External factors affecting construction project performance in Iraq using pestle factors - Khalid, Layth Salman (2020)
Construction industry is extremely dynamic sector and plays an important role in developing economy of a country, and in contribution to economic growth. However, construction projects face several risks that limit their progress, which frequently have negative effect on overall project performance in term of exceeding initial time and cost estimates. Most research only considered factors affecting the project performance that related to company specific or project specific and overlooked the external factors were in spite of their importance. Understanding those factors is vital for countries to avoid risks, regulate expenditures, and enhance project performance. This research aims to investigate the effect of the external factors on the performance of construction project in Iraq. The external factors are identified by using PESTLE technique. A conceptual model for the relation between the PESTLE factors and project performance is developed. The research utilizes a mix method comprising quantitative and qualitative approaches to collect the required data. The quantitative approach used a survey questionnaire involving 127 respondents selected from several construction companies in Iraq to evaluate the conceptual model and develop the SEM model using the PLSSEM for data analysis. The qualitative approach used an interview with several experts in construction industry in Iraq for further insight to support the questionnaire findings. The interview data is analyzed using content analysis. The SEM model evaluation results indicated the reliability of the model. The results of the questionnaire data analysis indicate that all PESTLE factors have significant effects on performance but in different extents. Economic, and technological followed by political factors have larger effects on project performance. The results also indicated that more than 64.8 % of performance in terms of cost, time, and quality can be attributed to PESTLE effect. The interview analysis is consistence with the survey findings. The SEM model was verified by several experts in the construction industry, and the findings resulted economic, and technological followed by political factors have larger effects on project performance its ability to define the structural relations between the PESTLE factors and the project performance in Iraq construction industry. The findings of this research help governments to put regulations, policies, and strategies to avoid or mitigate PESTLE factors effect in case of their occurrence. Therefore the effectivness to manage risks, control expenses, increase competitiveness and improve the quality of project is more manageable and systematic